Pengaruh Pengembangan Sumber Daya Manusia dan Sarana Prasarana terhadap Kualitas Pelayanan di Balai Pelestarian Kebudayaan Wilayah XX Maluku - Loupatty, Stenli Reigen; Rahawarin, Mohamad Arsad; Laurens, Samson (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the effect of Human Resource Development (HRD) and Infrastructure on Service Quality at the Cultural Heritage Preservation Office (Balai Pelestarian Kebudayaan) Region XX Maluku. The research uses a quantitative approach with multiple linear regression methods to test three hypotheses, both partially and simultaneously. The sample consisted of all employees in the institution, with a total of 93 respondents. The results of the analysis show that HRD has a significant effect on improving service quality. Similarly, adequate infrastructure also contributes significantly to the efficiency and effectiveness of services. Simultaneously, these two independent variables significantly influence service quality, as evidenced by a coefficient of determination (R²) value of 0.800. This means that 80% of the variation in service quality can be explained by HRD and infrastructure factors. The findings provide essential recommendations for policymakers to enhance HR quality through training programs and provide supportive work facilities. Moreover, the synergy between HRD and infrastructure needs to be managed in an integrated manner to achieve optimal public services. The study also recommends regular evaluations to ensure that service quality improvements are continuous and adaptive to future challenges.